A Review of Observations of Molecular Ions in the Earth’s Magnetosphere-Ionosphere System - Lin, Mei-Yun; Ilie, Raluca (Frontiers in Astronomy and Space Sciences, 2022)
Ionospheric molecular ions, such as NO⁺, N₂⁺ and O₂⁺, are gravitationally bound, and are expected to undergo recombination to form a pair of neutral atoms, due to short dissociative recombination lifetime. Therefore, they are considered to be rather cold in the Earth’s atmosphere, compared with light ions such as H⁺ and He⁺, or even heavier ions such as N⁺ or O⁺. However, several spacecraft missions observed their presence in the high-altitude ionosphere and the magnetosphere, predominantly during the geomagnetically active times. This hints to the possibility that molecular ions have the ability to acquire sufficient energy in a very short time, and can be used as tracers of mass differentiated vertical transport to understand the mechanisms responsible for "fast ionospheric outflow". In this letter, we review the observational data sets that reported on the abundances of molecular ions in the Earth’s magnetosphere-ionosphere system, starting from their first observations by the Sputnik III mission, to current Arase (ERG) satellite and Enhanced Polar Outflow Probe (e-POP) missions. The available data suggests that molecular ions are quite abundant in the lower atmosphere at all times, but are only seen in the high-altitude ionosphere and magnetosphere during the times of increased geomagnetic activity.